Personalized ophthalmology. (July 2014) - Porter, L.F.; Black, G.C.M.
<x xml:space="preserve">Abstract</x> Ophthalmology has been an early adopter of personalized medicine. Drawing on genomic advances to improve molecular diagnosis, such as next‐generation sequencing, and basic and translational research to develop novel therapies, application of genetic technologies in ophthalmology now heralds development of gene replacement therapies for some inherited monogenic eye diseases. It also promises to alter prediction, diagnosis and management of the complex disease age‐related macular degeneration. Personalized ophthalmology is underpinned by an understanding of the molecular basis of eye disease. Two important areas of focus are required for adoption of personalized approaches: disease stratification and individualization. Disease stratification relies on phenotypic and genetic assessment leading to molecular diagnosis; individualization encompasses all aspects of patient management from optimized genetic counseling and conventional therapies to trials of novel DNA‐based therapies. This review discusses the clinical implications of these twin strategies. Advantages and implications of genetic testing for patients with inherited eye diseases, choice of molecular diagnostic modality, drivers for adoption of personalized ophthalmology, service planning implications, ethical considerations and future challenges are considered. Indeed, whilst many difficulties remain, personalized ophthalmology truly has the potential to revolutionize the specialty.